Attitudes and beliefs as verbal behavior - Guerin, Bernard (1994)
Attitudes and beliefs are analyzed as verbal behavior. It is argued that shaping by a verbal community is an essential part of the formation and maintenance of both attitudes and beliefs, and it is suggested that verbal communities mediate the important shift in control from events in the environment (attitudes and beliefs as tacts) to control by other words (attitudes and beliefs as intraverbals). It appears that both attitudes and beliefs are constantly being socially negotiated through autoclitic functions. That is, verbal communities reinforce (a) reporting general rather than specific attitudes and beliefs, (b) presentation of intraverbals as if they were tacts, and (c) presentation of beliefs as if they were attitudes. Consistency among and between attitudes, beliefs, and behavior is also contingent upon the reinforcing practices of verbal communities. Thus, attitudes and beliefs can be studied as social behavior rather than as private, cognitive processes.